2011
DOI: 10.1007/s11033-011-0767-5
|View full text |Cite
|
Sign up to set email alerts
|

The C/A polymorphism in intron 11 of the XPC gene plays a crucial role in the modulation of an individual’s susceptibility to sporadic colorectal cancer

Abstract: Abstract:Background: Epidemiological data show that colorectal cancer (CRC) is the second most frequent malignancy worldwide. The involvement of "minor impact genes" such as XME and DNA-repair genes in the etiology of sporadic cancer has been postulated by other authors.Aim: we focused on analyzing polymorphisms in DNA-repair genes in CRC. We considered the following genes involved in DNA-repair pathways: base excision repair (OGG1 Ser326Cys, XRCC1 Trp194Arg and Arg399Gln); nucleotide excision repair [XPA (-4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 56 publications
4
51
0
Order By: Relevance
“…Four publications were excluded because of meta-analysis, control group had cancer patients or not published in English. Finally, 26 full-text articles with eligibility were included in this meta-analysis (Smith et al, 2003;Huang et al, 2006;Mechanic et al, 2006;Moreno et al, 2006;Crew et al, 2007;Jorgensen et al, 2007;Chang et al, 2008;Hung et al, 2008;McWilliams et al, 2008;Rajaraman et al, 2008;Abbasi et al, 2009;Han et al, 2009;Joshi et al, 2009;Agalliu et al, 2010;Rajaraman et al, 2010;Doherty et al, 2011;Krupa et al, 2011;Smith et al, 2011;Gil et al, 2012;Yu et al, 2012;Cheng et al, 2013;Santos et al, 2013;Wang et al, 2013;Wyss et al, 2013;Kohlhase et al, 2014;Steck et al, 2014). The flow chart which reflected the details of article selection was presented in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four publications were excluded because of meta-analysis, control group had cancer patients or not published in English. Finally, 26 full-text articles with eligibility were included in this meta-analysis (Smith et al, 2003;Huang et al, 2006;Mechanic et al, 2006;Moreno et al, 2006;Crew et al, 2007;Jorgensen et al, 2007;Chang et al, 2008;Hung et al, 2008;McWilliams et al, 2008;Rajaraman et al, 2008;Abbasi et al, 2009;Han et al, 2009;Joshi et al, 2009;Agalliu et al, 2010;Rajaraman et al, 2010;Doherty et al, 2011;Krupa et al, 2011;Smith et al, 2011;Gil et al, 2012;Yu et al, 2012;Cheng et al, 2013;Santos et al, 2013;Wang et al, 2013;Wyss et al, 2013;Kohlhase et al, 2014;Steck et al, 2014). The flow chart which reflected the details of article selection was presented in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Associations between six single-nucleotide polymorphisms (SNPs) of the earlier-mentioned five genes and CRC have been reported in different ethnic groups (Smith et al, 2001;Landi et al, 2003Landi et al, , 2005Krzesniak et al, 2004;Jiang et al, 2005;McGreavey et al, 2005;Murtaugh et al, 2005;Slattery et al, 2005Slattery et al, , 2006Berndt et al, 2006;Huang et al, 2006;Koh et al, 2006;Kuriki et al, 2006;Matsuo et al, 2006;Moreno et al, 2006;Theodoropoulos et al, 2006;Tranah et al, 2006;Hansen et al, 2007;Kang et al, 2007;Stern et al, 2007;Vogel et al, 2007;Yin et al, 2007;Kury et al, 2008;Funke et al, 2009;Khatami et al, 2009;Tsilidis et al, 2009;Yang et al, 2009;Engin et al, 2010;Meplan et al, 2010;Loh et al, 2011;Wu et al, 2011;Crous-Bou et al, 2012;Gil et al, 2012). These six variants comprised rs12917 and rs2308321 of MGMT, rs1229984 of ADH1B, rs4880 of SOD2, rs2228001 of XPC, and rs1801282 of PPARG.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a subsequent study the same authors observed a lack of Thr241Met polymorphism impact on CRC risk [27]. A similar conclusion follows from the Gil et al investigation which found no statistical association in groups consisting of 133 CRC patients and 100 controls [28].…”
Section: Studies On the Polish Populationmentioning
confidence: 61%